Trends and Causes of Internal Migration: A Case Study of Ilam Municipality, Nepal - Adhikari, Kamal (DMC Research Journal, 2023)
This research work attempts to portray the increasing rate of migration in a particular area of Ilam Municipality. It focuses on the trends and causes of the internal migration in Ilam Municipality of Nepal from different parts of the country which is growing rapidly. It has faced so many challenges of overpopulation. It is considered as the civic duty to solve the existing problem of migration on time otherwise it results into a worsening condition. The appropriate ways for analyzing the causes of migration can be discussed in references with push and pull factors. The main push factor for migration is lack of employment opportunities, education, health and transportation facilities, low agricultural productivity, natural calamities, business failure, transfer of service, and land sold in the place of origin. Similarly, educational facilities, physical facilities, business opportunities, purchase of land, security, presence of relatives, and marriage are the main attractive factors for Internal Migration within Ilam municipality. The major consequences of Internal Migration appear as both in  positive and negative aspects in the destination, origin as well. Some of the positive aspects of migration in the Ilam municipality have a good income from the agricultural product, an increase in business activities, sharing of culture, and feelings of cooperation. In terms of negative aspects of migration in the municipality are deforestation, over  consumption of resources, pollution, fragmentation of land, and an increase in criminal or immoral activities.